Transfer of Care Between the Emergency Department and an Older People’s Mental Health Inpatient Unit - Rachael Elliott (BJPsych Open, 2025)
Aims: Two patients within an Older People’s Mental Health (OPMH) unit that had been transferred to the emergency department (ED) for physical health assessment were found to have returned without a handover or discharge letter. The discharge letters, received more than 48 hours later, revealed important interventions that were consequently delayed. This audit aimed to identify compliance with NICE Quality Standard QS174: adults admitted with a medical emergency and whose care is being transferred to a different healthcare setting have information about their condition and needs passed onto their new care provider.